Open innovation implementation pratices and firm competitiveness in Malaysian manufacturing industry - Ismail, Houssam Said Abdelrahman (2015)
Malaysia has successfully transformed from an agriculture -based economy into a resource-based economy. However, Malaysia’s endeavor to transform into an innovation-led economy is presently hindered by the lack of innovation capabilities important for business, as well as by the Malaysian policies’ lack of focus on modern concepts of innovation, such as open innovation. Despite the fact that the implementation of an open innovation concept will enhance the competence of innovation in the manufacturing sector; a theoretical framework for enhancing this implementation in Malaysia is still absent. Furthermore, the relationship between open innovation concept and firms’ competitiveness indicators is still unclear. This thesis determined the effectiveness of the local innovation policy, investigated the level of open innovation practices in the Malaysian manufacturing sector and identified the factors that influence the adoption of open innovation practices. The thesis also examined the relationship between implementing open innovation practices and firms’ competitiveness indicators. A quantitative method with a descriptive and inferential analysis was used to obtain the results of this research. The study population were 1100 manufacturing firms located in Selangor state. Based on the proposed framework which was developed by the author,a valid questionnaire was used in a self-administrated survey to collect the data. The questionnaires were answered by conducting face-to-face interviews with the participants. The participants were 281 manufacturing firms out of the 1100 firms in Selangor. The inferential analysis used was the Parametric Test (One-sample T-test), to investigate the factors included in the proposed framework. After data analyses, the author modified the proposed framework and revealed nine key factors affecting the adoption of open innovation in Malaysia. These factors were grouped into three main areas, intellectual property management in universities, government policies including laws and intellectual property management in industries. This research supports the claim that open innovation concepts have a positive impact on firms' performance, as the study revealed a significant relationship between open innovation adoption and firms’ competitiveness indicators. It was determined that if a firm increases the implementation of open innovation practices, its ability to compete in business will increase. Finally, the study showed that the Malaysian innovation policy has a significant influence on the innovation atmosphere. However, this policy needs improvement in order to support a modern approach to innovation.